Analisis Perubahan Gairaigo Bahasa Jepang dalam Asahi Shimbun (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2016)
This research focused on gairaigo that appeared in Asahi Shimbun newspaper articles published on April 15-21, 2014. The articles that used for this research was taken from several pages of the newspaper, such as main pages, economic pages, international pages, sport pages and social pages. Gairaigo that analyzed in this research was changed by four types of changes; the changes of a part of speech, the changes of the word form, the changes from the origin’s meaning, and the variation of loan word made in Japan (wasei-eigo).